A population based analysis of the implementation of pediatric facemasks in girls youth lacrosse. (February 2017) - Walls, Andrew; Kasle, David; Aaronson, Nicole; Harley, Earl; Waldman, Erik
Abstract: Objective: To determine the incidence, relative risk reduction, odds ratio and absolute risk reduction of head and ear injuries associated with the implementation of pediatric facial eye guards in lacrosse events. Study design: Cross Sectional Review of a National Database. Study location: National Emergency Injury Survelliance System. Methods: Our group retrospectively reviewed a nationwide sampling estimate of 809 patients who presented to emergency rooms with head and ear injuries during lacrosse events. The database was queried for lacerations, fractures, hemorrhages, abrasions and punctures associated with the face and ear. Incidence, relative risk, odds ratio and absolute risk reductions were calculated both five years before and five years after the introduction of the facial mask guard in 2006 to determine benefit. Results: Of the 809 women's lacrosse injuries, 199 were localized to the facial region and 56 to the ear. After the implementation of the facial mask mandate, there was a significant decrease in the total incidence and relative risk of facial lacerations (P = 0.01, RR = 0.08 vs 0.01) and facial abrasions (P = 0.02, RR = 0.28 vs 0.12) respectively. Furthermore, there was a significant decrease in the odds of obtaining a facial laceration (OR: 0.16 95% CI:0.07–0.37), facial fractures (OR: 0.01, 95% CI:0.03–0.35) and abrasion (OR: 0.11, 95% CI:0.08–0.18) with facemask use. Unfortunately, there was no difference in total incidence, relative risk or odds of obtaining ear injury. Conclusion: It appears that the implementation of the mandate for female athletes to utilize the facemask starting in 2006 has provided a reduction in specific facial injuries. Further discussion should be continued in order to reduce further risk to the remaining head and neck region including the ears and neck with additional protective equipment.